Female leadership and green M&As - Konkola, Annika (My University, 2025)
Green transition has increased the attention towards firm sustainability initiatives and the incorporation of environmental, social, and governance (ESG) factors. As a part of good governance, gender equality and diversity in corporate boards and other leadership positions has gained increased attention. The effect of female leadership has been studied in multiple contexts regarding corporate strategic decision making and firm sustainability initiatives. These have been found to be positively influenced by female leadership. This thesis extends the research by examining if this relationship exists in the context of green M&As. Firms are constantly adapting to changing operational environment, stakeholder demands, and regulatory frameworks, which requires creativity in strategic decision making. Green M&As are a developing strategic tool to adapt to these constant chances as they focus on acquiring green technologies, that enable acquirers to achieve their sustainability objectives. This thesis studies the influence of female CEOs on green M&A likelihood by utilizing data on M&A transactions completed by firms headquartered in the United States. The data includes samples on both green and non-green M&As from 2010 to 2023. To my best knowledge, this thesis is first to extend the research on CEO gender to the context of green M&As and to study the effect of CEO gender in terms of stock market reaction to green M&A announcements. These relationships are studied by utilizing multiple regression models. Four regression models are cross-sectional to find relationships in different contexts: industry pollution, environmental sensitiveness, firm transparency, and industry competitiveness. Additionally, this thesis investigates the stock market reaction to green M&A announcements. The stock market reaction is analyzed by calculating the market-model cumulative abnormal returns, utilizing the green M&A data to incorporate information on CEO gender. The findings support and confirm the hypotheses of this thesis. First, the effect of CEO gender is statistically significant across the regression models, thus supporting the hypothesis that female CEOs positively affect the likelihood of green M&As. Second, the results indicate that the effect of female CEO is stronger in highly competitive markets. The results for this hypothesis are positive but statistically insignificant. Third, the stock market reaction to green M&A announcements is positive regardless of CEO gender, thus supporting and confirming hypothesis 3. The analysis suggests that CEO gender, besides other CEO characteristics are stronger drivers of green M&As, rather than the financial conditions of firms. Additionally, the results highlight the complex nature of M&A strategies and that decisions are driven by multiple internal and external factors.

Vihreä siirtymä ja kestävä kehitys ovat lisänneet kiinnostusta yritysten toiminnan kestävyyteen sekä ympäristöllisten, sosiaalisten ja hallinnollisten (ESG) seikkojen huomiointiin. Osana hyvää hallintotapaa sukupuolten tasa-arvo ja monimuotoisuus hallituksissa sekä muissa johtotehtävissä on noussut keskeiseksi teemaksi. Naisten johtajuuden vaikutusta on tutkittu laajasti erilaisissa yhteyksissä huomaten sen vaikuttavan positiivisesti yritysten tekemiin kestävän kehityksen aloitteisiin. Tämä tutkimus laajentaakin tutkimusta yrityskauppojen yhteyteen selvittäen, lisääkö naisjohtajuus kestävien yrityskauppojen (green M&A) esiintymisen todennäköisyyttä. Kestävän kehityksen myötä yritykset joutuvat jatkuvasti sopeutumaan muuttuvaan toimintaympäristöön, sidosryhmien vaatimuksiin, sekä lainsäädäntöön. Kestävät yrityskaupat ovatkin yleistyvä strategia vastata näihin muutoksiin. Kestävien yrityskauppojen keskiössä on esimerkiksi uudenlaisen teknologian hankkiminen, jonka avulla yritykset voivat saavuttaa kestävään yritystoimintaan liittyvät tavoitteensa. Tässä tutkielmassa tarkastellaan naisjohtajuuden vaikutusta kestävien yrityskauppojen todennäköisyyteen. Tutkielmassa käytetään data Yhdysvaltalaisten listattujen yhtiöiden tekemistä yrityskaupoista vuosina 2010-2023. Aineisto kattaa sekä tavallisia että kestäviksi luokiteltuja yrityskauppoja ja tutkimus on toteutettu useita regressiomalleja hyödyntäen. Regressiomallien avulla naisjohtajuuden ja kestävien yrityskauppojen suhdetta tutkitaan monessa eri asiayhteydessä: toimialan saastuttavuus, ympäristöherkkyys, yrityksen toiminnan läpinäkyvyys sekä markkinan kilpalutilanne. Tämä tutkielma on ensimmäinen, joka tutkii naisjohtajuuden vaikutusta kestävän kehityksen aloitteisiin yrityskauppojen kontekstissa. Lisäksi tutkielmassa tarkastellaan osakemarkkinoiden reaktioita kestäviin yrityskauppoihin kumuloituneen epänormaalin tuoton avulla hyödyntäen osakeindeksidataa sekä kestävien yrityskauppojen aineistoa toimitusjohtajan sukupuolen sisällyttämiseksi tarkasteluun. Tulokset tukevat tutkielman hypoteeseja. Tulosten mukaan toimitusjohtajan sukupuolella on tilastollisesti merkitsevä positiivinen vaikutus kestävien yrityskauppojen todennäköisyyteen kaikissa regressiomalleissa, mikä tukee hypoteesia naisjohtajuuden positiivisesta vaikutuksesta. Toiseksi, naisjohtajuuden vaikutus näyttää olevan hieman voimakkaami kilpailluilla markkinoilla, mutta tulos ei ole tilastollisesti merkitsevä. Viimeiseksi, osakemarkkinareaktio kestäviin yrityskauppoihin on positiivinen toimitusjohtajan sukupuolesta riippumatta. Analyysi korostaa yrityskauppojen kompleksia luonnetta osoittaen, että monet sisäiset ja ulkoiset tekijät ohjaavat strategista päätöksentekoa.
Keywords: Green Mergers & Acquisitions, Female leadership, Gender diversity, Vihreät yrityskaupat, Naisjohtajuus, M&A